2013
DOI: 10.1016/j.ssc.2013.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mn–O–O–Mn superexchange pathways in a honeycomb lattice Mn oxide with small charge-transfer energy

Abstract: We investigated the electronic structure of layered Mn oxide Bi3Mn4O12(NO3) with a Mn honeycomb lattice by x-ray absorption spectroscopy. The valence of Mn was determined to be 4+ with a small charge-transfer energy. We estimated the values of superexchange interactions up to the fourth nearest neighbors (J1, J2, J3, and J4) by unrestricted Hartree-Fock calculations and a perturbation method. We found that the absolute values of J1 through J4 are similar with positive (antiferromagnetic) J1 and J4, and negativ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The low critical magnetic field suggests that the disordered ground state and the magnetic-field induced state are energetically close. The intrabilayer couplings were suggested to be important to explain the disordered ground state [20,21]. It was reported that an large intrabilayer antiferromagnetic nearest-neighbor coupling gives rise to dimerization [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low critical magnetic field suggests that the disordered ground state and the magnetic-field induced state are energetically close. The intrabilayer couplings were suggested to be important to explain the disordered ground state [20,21]. It was reported that an large intrabilayer antiferromagnetic nearest-neighbor coupling gives rise to dimerization [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that an large intrabilayer antiferromagnetic nearest-neighbor coupling gives rise to dimerization [22][23][24][25]. On the other hand, the frustrating further-neighbor interactions beyond those of second-neighbors both inplane and intrabilayer were suggested to cause the disordered state [18,21,[26][27][28][29]. Although these further-neighbor interactions should be important, the bilayer structure with many relevant interac- tions makes the detailed analysis of the inelastic neutron scattering results challenging.…”
Section: Introductionmentioning
confidence: 99%
“…An important and interesting aspect of low-dimensional compounds relates to superexchange pathways between magnetic ions via nonmagnetic ligands (e.g., O 2– ) or complex units like [VO 4 ] 3– . This can be described by a super exchange (SE), i.e., M O M, or by a supersuper exchange (SSE), i.e., M O–V–O M . Two-dimensional layered compounds of the type, AAg 2 M­[VO 4 ] 2 and ANa 2 M­[VO 4 ] 2 contain magnetic metal ions (M) on a triangular lattice, where magnetic ions are linked via the nonmagnetic [VO 4 ] 3– unit.…”
Section: Introductionmentioning
confidence: 99%
“…The BaAg 2 Mn­[VO 4 ] 2 compound is an example for the realization of frustrated triangular lattice antiferromagnet . The Cu 2+ compound is interesting because both ferromagnetic and antiferromagnetic interactions in one dimension (chain) are present and result in an intriguing behavior of their thermodynamic properties. , For further work on nontrivial ground states in low-dimensional spin-systems, see for example refs .…”
Section: Introductionmentioning
confidence: 99%
“…The lack of spontaneous magnetic ordering within the Mn honeycomb lattices down to very low temperature was proposed to be due to frustration of magnetic interactions, in particular a competition between first and second neighbor antiferromagnetic Mn-Mn exchange interactions 2 . Currently BMNO is therefore viewed as a model system with strongly fluctuating S=3/2 spins on honeycomb lattice, with a magnetic frustration that is due to the presence of longer-range antiferromagnetic exchange interactions [2][3][4][5][6][7][8] .…”
mentioning
confidence: 99%